Nursing care of an elderly bedridden patient after swallowing foreign body (1例高龄卧床患者吞食异物后的护理) - HAO Lin (郝林); LIU Wenjing (刘文静) (Association of Integrative Nursing, 2022)
This paper summarized the nursing management for a long-term bedridden elderly patient with nasal feeding diet complicated with various diseases. During the daily oral care, the patient swallowed the mouth care straw tip (silicone foreign body) accidentally. Given the old age and poor gastrointestinal function of the patient, targeted intervention was implemented followed by precisely locating foreign body. Comprehensive nursing measures including biochemical index monitoring, medication care and prevention of complications were carried out to ensure the successful removal of the foreign body (本文总结1例高龄、合并多种疾病且长期卧床的鼻饲饮食患者发生异物吞食事件的护理体会。老年人群胃肠功能减弱, 通过检查定位异物位置, 针对性采取消化道异物处理方式, 同时注意生化指标监测、用药以及并发症预防等细节护理, 以促进异物顺利排出体外。)